Analisis Faktor Risiko Kejadian Kelainan Refraksi Miopia Pada Pelajar SMA Nasional Makassar - Muharfian, Andi Muh.; Firman, Firman (Trends in Applied Sciences, Social Science, and Education, 2024)
Myopia is an eye refraction disorder that makes it difficult for sufferers to see clearly for objects that are located far away. The largest percentage of myopia cases in Indonesia from the Republic of Indonesia Ministry of Health data occurred at the age of students (11-20 years), which was 23.74% and from the results of myopia screening conducted at SMA Nasional Makassar students, myopia prevalence was 12.9%. This study aims to determine the risk factors for the incidence of myopia refraction abnormalities in SMA Nasional Makassar students. This type of research is observational quantitative analytic using a Case Control Study design with a sample size of 120 people where the case sample were 30 people and the control sample were 90 people . Case samples were obtained by total sampling technique and control samples were obtained by simple random sampling technique. Primary data collection with snellen cards and interviews using a questionnaire. The results showed reading activity (OR = 7.5; 95CI% = 2.1-26.6), risky activities using handphone (OR = 6.0; 95CI% = 1.3-27.0), risky activities using computer or laptop (OR = 3.3; 95CI% = 1.4-7.8), risky TV watching activities (OR = 3.1; 95CI% = 1.1-8.2), and family history ( OR = 2.6; 95CI% = 1.1-6.2). All of the independent variables in this study are risk factors for the case of myopia refraction in SMA Nasional Makassar students.